The 2014 Russian Invasion of Crimea: Identity and Geopolitics - Makio, Danielle [UNESP]; Fuccille, Alexandre [UNESP] (FapUNIFESP (SciELO), 2023)
The following paper aims to unveil the reasons behind the Russian annexation of Crimea in 2014. Based on the hypothesis that Moscow’s decision was the result of the combination of strategic and ideational drivers, the study demonstrates how President Vladimir Putin’s political project has: (i) deepened Russia’s rivalry towards the West, strengthening the threat posed by NATO’s expansion; (ii) and highlighted the role of memory in the state’s identity, putting Ukraine in a privileged position in the Kremlin’s political agenda.
Keywords: Crimea; Geopolitics; Identity; Russia; Ukraine